Numerical Simulation of Surface Subsidence and Backfill Material Movement Induced by Underground Mining - Xibing Li; Dongyi Wang; Chongjin Li; Zhixiang Liu (Advances in Civil Engineering)
Surface subsidence induced by underground mining is one of the challenging problems in mining engineering, which can destroy ground surface buildings and cause huge economic losses to the mine. In this study, a two-dimensional numerical model, established by the discrete element method code PFC2D, was adopted to investigate the mechanical mechanism of surface subsidence and backfill material movement induced by underground mining in the Hongling lead-zinc mine. In the first simulation case, the ore body was excavated from the ground surface to the mining level 705 m by the sublevel caving mining method, and the stress evolution during the mining process was analyzed to reveal the mechanical mechanism of surface subsidence. In the second and third simulation cases, the mined-out areas above 905 m were backfilled by the noncemented tailings and an insulating pillar was reserved beneath the backfill material, and then the deep ore body was excavated by two different mining methods to study the movement law of the backfill material and rock strata induced by underground mining. The numerical simulation results show that when the sublevel caving mining method is adopted, underground mining can induce toppling failures in the hanging wall and lead to a large collapse pit in the ground surface. After the toppling failures in the hanging wall, the collapsed waste rock in the mined-out area can provide support force for the surrounding rock and restrict the further collapse of the hanging wall. Furthermore, when the cut-and-fill mining method is adopted for the excavation of deep ore body, the insulating pillar can restrict the horizontal displacement of surrounding rock and maintain the stability of the backfill material. The cut-and-fill mining method can efficiently control the surface subsidence and prevent the occurrence of collapse pit in the ground surface and is recommended for the Hongling lead-zinc mine to solve the surface subsidence problem.